Stress in frontline nursing professionals Covid-19 (Research, Society and Development, 2022)
Objectives: To analyze the stress that the nursing team suffered on the front line in the Covid-19 pandemic. Method: This is an integrative review carried out in October 2021, in the following databases: Latin American and Caribbean Literature on Health Sciences, Medical Literature Analysis and Retrieval System Online and Nursing Database. The searches were carried out using the Health Sciences Descriptors from the Regional Library of Medicine: Nursing, occupational stress, stress and Covid-19, with the help of the Boolean operators “AND” and “OR”. Results/Discussion: As results of the search in the databases, 17 studies were identified, which were discussed for analysis purposes, whose results were grouped and discussed in thematic categories, namely: factors associated with stress in nursing professionals in line with front of Covid-19 and mechanisms for reducing stressors in frontline Covid-19 professionals. Conclusion: The studies show a high rate of psychic alterations and physical exhaustion of these professionals who deal with Covid-19, and its challenges, practical techniques in the face of a global disaster, in which fear prevails causing psychological changes.